1965
DOI: 10.4039/ent97978-9
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and Field Investigations on the Ability of Eggs of the European Pine Sawfly, Neodiprion sertifer (Geoffroy) to Withstand Low Winter Temperatures

Abstract: Measurements of the supercooling points of eggs from different latitudes suggest that the cold-hardiness of N. sertifer is increased by the selective pressure of low winter temperatures. In Ontario, the insect is only beginning to experience temperatures capable of influencing population trends, but the selection of a more cold-hardy population may be in progress. It is predicted that this insect will eventually be capable of extendng its range into natural stands of jack pine in the northwestern portion of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

1966
1966
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 17 publications
(13 reference statements)
2
29
0
Order By: Relevance
“…In Canada, the fall cankerworm, Alsophila pometaria (Harris), has a lower SCP in the Temperate Dry climate of Alberta (-44.6°C;Sømme, 1964), than in the Temperate Cold Continental climate of Nova Scotia (-37.2°C;MacPhee, 1964). The SCP of Neodiprion pratti banksianae Rohwer in Canada is higher in the Temperate Cold Continental zone (-34.0°C) than that in the colder Boreal Continental zone (-39.1°C) (Sullivan, 1965). The European elm bark beetle, Scolytus multistriatus (Marsham), freezes at a higher temperature in the Temperate Cold Continental climate of Michigan, USA, (-24.1°C; Truchan & Butcher, 1970) than in the colder Boreal Continental zone of mid-Asia (-53.0°C; Lozina-Lozinskii, 1974).…”
Section: Variation Within Species Among and Within Climatic Zonesmentioning
confidence: 99%
See 3 more Smart Citations
“…In Canada, the fall cankerworm, Alsophila pometaria (Harris), has a lower SCP in the Temperate Dry climate of Alberta (-44.6°C;Sømme, 1964), than in the Temperate Cold Continental climate of Nova Scotia (-37.2°C;MacPhee, 1964). The SCP of Neodiprion pratti banksianae Rohwer in Canada is higher in the Temperate Cold Continental zone (-34.0°C) than that in the colder Boreal Continental zone (-39.1°C) (Sullivan, 1965). The European elm bark beetle, Scolytus multistriatus (Marsham), freezes at a higher temperature in the Temperate Cold Continental climate of Michigan, USA, (-24.1°C; Truchan & Butcher, 1970) than in the colder Boreal Continental zone of mid-Asia (-53.0°C; Lozina-Lozinskii, 1974).…”
Section: Variation Within Species Among and Within Climatic Zonesmentioning
confidence: 99%
“…There are large differences among populations of Neodiprion sertifer Geoffr. within the Temperate Cold Continental climate of Estonia and Latvia, -34.1°C (Sullivan, 1965); -39.1 to -40.6°C (Kopvillem & Kuusik, 1971;Merivee, 1978) but not among populations in Japan and Canada (-30.8° and -32.1°C) or between those and populations in the Temperate Highlands of Europe (-30.1 to -32.0°C) (Sullivan, 1965). Similar differences occur between populations of D. radicum from Estonia (-25.2°C;Merivee, 1978) and Leningrad (ca -21°C; Koš ál, 1993) but Turnock et al (1998) found no relationship between the SCP and the mean January air temperature for populations of this species from different locations and climatic zones.…”
Section: Variation Within Species Among and Within Climatic Zonesmentioning
confidence: 99%
See 2 more Smart Citations
“…Bale, 1991;Sinclair, 2001) and with the SCPs of some overwintering insects (e.g. Green, 1962;Sullivan, 1965;Tenow & Nilson, 1990;Turnock & Fields, 2005). The approach is also transferable to micro-modelling of mortality risk (cf.…”
Section: Discussionmentioning
confidence: 99%